The Influence Of Absence Of Students On The Quality Of Performance In Tests And Exams - K. AlDulaimy, Imad; J. AlQaysi, Bilal (Opción, 2019)
The research seeks to indicate the influence of the absence of students from attending the lectures. Department of Business Administration at the College of Almamoun University College is chosen to be the material of study, to de- termine the influence of the absence of students on the performance in the tests and exams in the academic year 2018 - 2019. The number of students of morning studies is (192) students (138) of whom are males and the rest are (54) females. The total number of evening students, there are (142) students, (109) of whom are males and the rest are (33) female students. The number of students of evening studies is (142) students (109) of whom are males and the rest are (33) females, thus, the total number of students under study is (334) students (247) of whom are males and (87) females. The collected indicative in- formation are based on the absenteeism rates for each student in the morning and evening studies , as well as the marks scored by each student during the first and second semesters. The study of the influence of absence on the marks scored by each student, on the one hand, for the purpose of showing the extent of gender (male and female) influence, on the other hand, are both taken into consideration, as well as to indicate whether the type of study (morning or evening) has any influence on the performance in a test as well as the rate of absence.